Vernacularism as an Essential Research Methodology in Translation Studies (Mesopotamian Journal of Arabic Language Studies, 2025)
This paper examines the transformative role of Vernacularism as introduced by Nasser Hajjaj in Arab Vernacularism (2024) (المحلية العربية) and its fundamental contributions to translation studies. As a newly coined term in the field, Vernacularism reshapes translation theory by offering an alternative to prescriptive linguistic approaches. By redefining the term "vernacular" and introducing new terminologies such as Tantīq (تنطيق) (transliteration), Shawārid (شوارد لغوية) (idiomatic expressions), and Ḩis’Chah (حسچة) (witty, symbolic, and enigmatic expressions in Iraqi vernacular), Hajjaj foregrounds the integration of cultural and linguistic nuances into translation. This methodology enhances the translation of creative works, particularly poetry, while simultaneously resisting cultural homogenization and preserving local identities. The paper argues that Vernacularism is indispensable in ensuring that translations maintain linguistic accuracy and cultural resonance, offering a framework for bridging cultures while counteracting hegemonic linguistic forces.